LEXICAL COHESION FOUND IN STAND-UP COMEDY: JOE LIST - Dewa Ayu Kadek, Claria (SIGEH ELT : Journal of Literature and Linguistics, 2026)
The title of this research is "Lexical Cohesion Found in Stand-up Comedy: Joseph Alberth List.”  Lexical cohesion is about meaning in the text. Lexical cohesion is a complex and variable relationship that needs to be understood within the context of a broader semantic overview of the English language. Lexical cohesion is grouped into five types. Research on lexical cohesion needs to be conducted, focusing on identifying the types and functions present in Joe List's stand-up comedy video on YouTube. The theory used is the theory of lexical cohesion types taken from Cohesion in English by Halliday and Hassan (1976). Then, supporting theories are used to answer the problem of the function of lexical cohesion from Halliday 1975 in the book Learning How to Mean. This study uses a YouTube video from Comedy Central Stand Up entitled “I Hate My Self” by Joe List. The data were collected by repeatedly watching the stand-up comedy video on YouTube. Then, a detailed transcript was made based on the YouTube video. Eventually, the data were classified and identified based on the theory applied. The results of the study show that five types of lexical cohesion are found in Joe List's Stand-up Comedy. The five types of lexical cohesion found are repetition, synonym, superordinate, general words, and collocation. Also, not all functions are found in Stand-up Comedy by Joe List. The functions found are informative, interactional, personal, and heuristic functions.